WAYS TO IMPLEMENT THE VOLUME OF PRODUCTION AND SALES OF PRODUCTS IN THE FINANCIAL MARKET THROUGH INTEREST AND PROFITABILITY RATES - Firdavs Farxod ugli, Kazakov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In the final part of the analysis of product production and sales, it is necessary to determine the possibilities of increasing the volume of the product at the expense of the internal possibilities that have not been used. Opportunities to increase product production and sales are improvements in the use of enterprise resources that have a quantitative dimension. We systematically search for additional opportunities to increase the volume of production and sales.